GADOLINIUM LIMITS MYOCARDIAL INFARCTION IN THE RAT: DOSE-RESPONSE, TEMPORAL RELATIONS AND MECHANISMS - Nicolosi, Alfred C. (2007)
The lanthanide cation, gadolinium (Gd) attenuates post-ischemic myocardial stunning. This study tests the hypothesis that Gd also preconditions the myocardium against infarction following ischemia-reperfusion (IR), and explores potential mechanisms underlying Gd-induced cardioprotection. Regional myocardial infarction was induced in rats by occluding the left anterior descending artery for 30 minutes and reperfusing for 120 minutes. Rats (n = 6/group) were administered intravenous Gd (1 to 100 μmol/kg) 15 minutes prior to ischemia. Hearts were excised after reperfusion to determine infarct size (IS) and area at risk (AAR). The ratio IS/AAR (%) was reduced by Gd in a “U”-shaped, dose-dependent manner. The minimum dose that reduced IS/AAR was 5 μmol/kg (52 ± 5% vs. 64 ± 4%), while the dose that reduced IS/AAR maximally was 20 μmol/kg (44 ± 4%). Gd also reduced IS/AAR when given 1 minute before reperfusion (47 ± 3%) but not when given 10 seconds after reperfusion (60 ± 3%). Cardioprotection was maintained if I-R was delayed 24–72 hours after Gd administration. Cardioprotection by Gd was abolished by inhibition of JAK-2 with AG-490, of p42/44 MAPK with PD98059 or of K(ATP) channels with glibenclamide. None of these agents given alone altered IS/AAR compared with controls. Inhibition of JAK-2 also blocked Gd-induced delayed cardioprotection. Gd may have broad potential roles in IR, as it confered immediate cardioprotection when given prior to ischemia or prior to reperfusion, and delayed cardioprotection for up to 72 hours after administration. The mechanism underlying Gd-induced preconditioning appears to be multi-factorial, involving JAK-2, STAT-3 and p44 MAPK pathways, as well as K(ATP) channels.